Impact of Magnesium and Ferritin Deficiency on Depression Among Adolescent Students - Amany H. Abdelmoneam; Ghada M. Khafagy; Khaled A Elbeh; Marwa D. A. Hasan (SAGE Publishing, 2024)
Background: Depression is considered the fourth-leading cause of health problems. It is the fourth-leading cause of health problems and disability, which causes 16% of the worldwide burden of disease and injury among adolescents. Objective: The aim of the present study was to evaluate the possible association of magnesium (Mg) and ferritin deficiency with depression in adolescent students. Patients and Methods: This case control study in secondary schools at Al-Ghanayem discrete. The total number included was 358 students. All were screened for depression by the Arabic version of the Beck questionnaire. The students who had positive score was selected as cases 86 and a matched same number of students with negative score was selected as controls. Serum level of ferritin and magnesium was measured in the 2 groups. Results: There was statistically significant difference between the studied groups when comparing depression grade with each of ferritin and Mg Depressed group cases had lower mean values of ferritin and Mg. The ferritin cut-off level for the prediction of depression was (35.5 μg/dL, which had a sensitivity of 74.4% and a specificity of 75.6%. The magnesium cut-off levels for the prediction of depression were1.95 mg/dL and 104.5 ng/dL which had a sensitivity of 70% and 64%, respectively. Conclusion: There was a statistically significant negative correlation between depression severity and each of socio-economic status ferritin and Mg. Each of ferritin and Mg were predictors for depression.